Visual communication in social play of a hierarchical carnivore species: the case of wild spotted hyenas. Issue 4 (16th September 2021) - Nolfo, Andrea Paolo; Casetta, Grazia; Palagi, Elisabetta
Abstract: Communication relies on signals that can be produced via different sensory modalities to modify receivers' behavior. During social interactions, the possibility to perceive subtle visual cues enhances the use of facial expressions to exchange information. One of the most appropriate fields to explore the specific design features of visual signals is play fighting. Here, we explored the production and potential role of Relaxed Open Mouth (ROM) and Head Bobbing (HB) in regulating play fighting of wild spotted hyenas Crocuta crocuta, a highly hierarchical carnivore species. In accordance with the assumptions of the signal optimization theory, wild hyenas produced ROM and HB almost exclusively when the sender was in direct visual contact with the receiver thus suggesting that senders were attentive to the playmates' face. Contrary to HB, the sequential analysis revealed that ROM often anticipated offensive patterns such as play biting thus supporting the hypothesis that ROM, but not HB, is a metacomunicative signal. Moreover, when the offensive patterns were biased toward one of the 2 players, the session was punctuated by a higher number of ROMs. Our findings support the general hypothesis that these 2 visual signals can play different roles in the management of play fighting in this carnivore species. The complementary use of ROM and HB would suggest that spotted hyenas are highly competent and fast in processing facial displays of different nature to correctly "read others' intentions" and respond with appropriate motor actions to avoid misunderstanding during one of the most multifaceted and risky social interaction.